Arribando aos Mururus Os pescadores de Tefé na fronteira do desenvolvimento sustentável - SOUSA, Arinaldo Martins de (2005)
an outline of anthropological analysis in ecology policy, tries, in good faith to address. Like any sticker, she tries to act as a sign: narrative of real events that happened during a trip by myself with fishermen and held in November 2004 but told tendentiously to mean. The elements are: a boat in poor condition; month November in the Middle Solimões, fishermen with a problem to solve, a anthropologist, a paraná to be sailed, macrophytes.